Using Virtual Reality in the Inference-Based Treatment of Compulsive Hoarding - St-Pierre-Delorme, Marie-Eve; O’Connor, Kieron (Frontiers in Public Health, 2016)
The present study evaluated the efficacy of adding a virtual reality (VR) component to the treatment of compulsive hoarding (CH) following inference based therapy. Participants were randomly assigned to either an experimental or a control condition. Seven participants received the experimental and seven received the control condition. Five sessions of one hour were administered weekly. A significant difference indicated that the level of clutter in the bedroom tended to diminish more in the experimental group as compared to the control group F(2,24) = 2.28, p = .10. In addition, the results demonstrated that both groups were immersed and present in the environment. The results on post-treatment measures of CH (Saving Inventory revised, Saving Cognition Inventory and Clutter Image Rating scale) demonstrate the efficacy of inference based therapy in terms of symptom reduction. Overall, these results suggest that the creation of a virtual environment may be effective in the treatment of CH by helping the compulsive hoarders take action over they're clutter.